Do commercial serologic tests for Trypanosoma cruzi infection detect Mexican strains in women and newborns? - Gamboa-León, Miriam (2011)
Fil: Gamboa-León, Rubi. Tulane University. School of Public Health and Tropical Medicine; Estados Unidos.